Deep Intronic LINE-1 Insertions in NF1: Expanding the Spectrum of Neurofibromatosis Type 1-Associated Rearrangements - Alesi, Viola; Genovese, Silvia; Lepri, Francesca Romana; Catino, Giorgia; Loddo, Sara; Orlando, Valeria; Di Tommaso, Silvia; Morgia, Alessandra; Martucci, Licia; Di Donato, Maddalena; Digilio, Maria Cristina; Dallapiccola, Bruno; et al. (Biomolecules (Basel, Switzerland), 2023)
Neurofibromatosis type 1 is an autosomal-dominant condition caused by NF1 gene inactivation. Clinical diagnosis is corroborated by genetic tests on gDNA and cDNA, which are inconclusive in approximately 3–5% of cases. Genomic DNA approaches may overlook splicing-affecting intronic variants and structural rearrangements, especially in regions enriched in repetitive sequences. On the other hand, while cDNA-based methods provide direct information about the effect of a variant on gene transcription, they are hampered by non-sense-mediated mRNA decay and skewed or monoallelic expression. Moreover, analyses on gene transcripts in some patients do not allow tracing back to the causative event, which is crucial for addressing genetic counselling, prenatal monitoring, and developing targeted therapies. We report on a familial NF1, caused by an insertion of a partial LINE-1 element inside intron 15, leading to exon 15 skipping. Only a few cases of LINE-1 insertion have been reported so far, hampering gDNA studies because of their size. Often, they result in exon skipping, and their recognition of cDNA may be difficult. A combined approach, based on Optical Genome Mapping, WGS, and cDNA studies, enabled us to detect the LINE-1 insertion and test its effects. Our results improve knowledge of the NF1 mutational spectrum and highlight the importance of custom-built approaches in undiagnosed patients.